STUDI KEARIFAN LOKAL PENANAMAN PADI DI DESA TEBING TINGGI KABUPATEN KUANTAN SINGINGI - Narmi Lisdiana; Eri Sayamar; Cepriadi Cepriadi (Fakultas Pertanian, Universitas Riau, 2018)
The purpose of this research were: (1) to examine the existing local wisdom that still exist in thecultivation of rice field in Tebing Tinggi Village, Benai Sub-district of Kuantan SingingiDistrict and (2) to observe the level of importance and the level of local farmer's wisdom in ricefield cultivation in the Village Tebing Tinggi Sub District of Benai Kuantan Singingi District.The sample were 30 respondents from Tebing Tinggi Village. Sampling technique used wasSnowball Sampling. The data analysis was conducted descriptively and then converted to LikertScale's Summated Rating (SLR) and Cartesian Diagram. The results show that there are 60 localwisdom conducted by rice farmers in Tebing Tinggi Village, consisting of 30 wisdom that onceexisted but not maintained, 29 wisdom that once existed and still maintained, and one newwisdom and still maintained. Based on the results of the level of importance and strength oflocal wisdom of rice farmers are located in Quadrant II which means the level of importanceand strength of the wisdom are above average (high).